O conceito de símbolo em Sidman e Skinner - uma análise epistemológica - Rocca, Julia Zanetti (2012)
The theory of language created by Skinner in the 1950s rejected traditional terms such as reference , meaning and symbol , due to considering such terms useless and inadequate to a science of verbal behavior. Still, since the 1960s new theories of language in behavioral analysis have come to make use of these terms both to describe phenomena and to define concepts. In order to investigate this theoretical dissonance, the present work analyses the concepts of reference , meaning and symbol in the theories of Skinner and Sidman. In regards to Skinner, the investigation has implied in (I) the analysis of the theories of language that have exerted influence on his work in order to understand the rejection of both reference and symbolism; (II) the description of the theoretical path of construction of a science of verbal behavior through an operationalist conception of language. In the case of Sidman, the theory of language arises as a result of experimental discoveries, which by its turn demanded from the conceptual investigation: (I) the description of the origin of the technical terms used in the field through Sidman s and his predecessor s researches; (II) the analysis of potential theoretical influences upon conceptual formalization of the stimulus equivalence paradigm. As the result, it has been verified that the theories of both Sidman and Skinner share the influence of the logical branch of the Philosophy of Language, and especially of the Logical Positivists. However, while Sidman s work is close to these philosopher s initial theories, Skinner s work is characterized as critical in relation to them. Moreover, the epistemological analysis of the stimulus equivalence paradigm has allowed the conclusion that this model adopts strictly operationalist presuppositions, and beyond that, of an Skinnerian Operationalism that is to say, different both from Bridgman s original version and from other psychological versions, such as Stevens . And since Operationalism would be the most important basis for the analysis of language proposed by Skinner, the conceptual differences between the theories of Sidman and Skinner appear to coexist with a confluence in their epistemological foundations.